2010
DOI: 10.1183/09031936.00142010
|View full text |Cite|
|
Sign up to set email alerts
|

Reproducibility of 6-minute walking test in patients with COPD

Abstract: The reproducibility of the 6-min walking test (6MWT) needs to be more solidly studied. This study aimed to investigate the reproducibility of two 6MWTs performed on subsequent days in a large and representative sample of patients with chronic obstructive pulmonary disease (COPD), and to quantify the learning effect between the two tests, as well as its determinants.In a retrospective observational study, 1,514 patients with COPD performed two 6MWTs on subsequent days. Other measurements included body compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
155
9
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 31 publications
16
155
9
6
Order By: Relevance
“…This indicates that, for this population, the test is reproducible with reproducibility values similar to those obtained using other clinical exercise tests, such as 6-min walk test, which presents an ICC of 0.88 -0.94, [20][21][22] and shuttle-walk test, which presents an ICC of 0.87. 23 Moreover, the error value for this comparison was acceptable, presenting a mean error of 5.7 steps and limits of agreement ranging from Ϫ7.1 to 18.6 steps.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This indicates that, for this population, the test is reproducible with reproducibility values similar to those obtained using other clinical exercise tests, such as 6-min walk test, which presents an ICC of 0.88 -0.94, [20][21][22] and shuttle-walk test, which presents an ICC of 0.87. 23 Moreover, the error value for this comparison was acceptable, presenting a mean error of 5.7 steps and limits of agreement ranging from Ϫ7.1 to 18.6 steps.…”
Section: Discussionmentioning
confidence: 48%
“…This characteristic could be an advantage over the 6-min walk test, which requires at least one previous test and a recovery time between them, totaling a time expenditure of at least 50 min. 20 However, since the 6-min walk test has been largely used, and it has already been validated and related to morbidity/mortality in COPD subjects, we suggest that 6MST should substitute for the walk test only under certain circumstances. The 6MST should be used when there is not an adequate area in which to perform it or when the time is too short to allow a Values are expressed as mean Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are in agreement with Stevenson et al [26], indicating that the resolution of COPD exacerbation is related to increased values of operating lung volumes (FEV 1 , IC). Moreover, in our study we found that a relatively small, but significant improvement in RV%TLC (-4%) and FEV 1 (+200 mL) may be accompanied by major (+121 m) improvement in 6MWT result, which is much higher than generally accepted as clinically significant [27,28]. Another possible explanation for positive correlation of FEV 1 and exercise is the fact that significant improvement of FEV 1 is usually not observed in stable COPD.…”
Section: Discussionmentioning
confidence: 39%
“…The minimal oxygen saturation during 6MWT in our study was significantly higher after treatment, when compared with baseline values. These data are of importance as they indicate that increased exercise tolerance was due to respiratory improvement and not due to the doctor forcing the patient to march faster or due to the patient's learning potential [28]. As expected, IC has not revealed the degree of hyperinflation, whereas RV%TLC, as one of the most accurate methods of measuring hyperinflation, could reflect static hyperinflation changes [27,29].…”
Section: Discussionmentioning
confidence: 90%